2018
DOI: 10.1002/mbo3.609
|View full text |Cite
|
Sign up to set email alerts
|

Mycobiota of maize seeds revealed by rDNAITS sequence analysis of samples with varying storage times

Abstract: Fungi are an integral component of the plant microbiome. However, the composition and variation in the fungal communities (mycobiota) associated with seeds are poorly understood. In this study, we investigated the mycobiota of 11 maize seed samples with storage times ranging from 6 months to 12 years. Mycobiota were characterized by a culture-based approach, and fungal species were identified through rDNA-ITS sequence analyses. From a total of 169 pure fungal isolates obtained from both the seed surface and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 58 publications
2
22
0
Order By: Relevance
“…with incidences of up to 7.33%, 2.45%, 16.09%, 21.33%, 12.50% and 6.54%, respectively (Figure 1). These accompanying species are common mycobiota on maize kernels in Serbia and worldwide and already confirmed in some previous studies (Krnjaja et al, 2004;Tančić, 2009;Mendoza et al, 2017;Xing et al, 2018;Tóth et al, 2012). The lower incidence of Aspergillus and Penicillium species in the present study is consistent with the findings of Rodríguez Páez et al 2011, who also detected Penicilium spp.…”
Section: Resultssupporting
confidence: 93%
“…with incidences of up to 7.33%, 2.45%, 16.09%, 21.33%, 12.50% and 6.54%, respectively (Figure 1). These accompanying species are common mycobiota on maize kernels in Serbia and worldwide and already confirmed in some previous studies (Krnjaja et al, 2004;Tančić, 2009;Mendoza et al, 2017;Xing et al, 2018;Tóth et al, 2012). The lower incidence of Aspergillus and Penicillium species in the present study is consistent with the findings of Rodríguez Páez et al 2011, who also detected Penicilium spp.…”
Section: Resultssupporting
confidence: 93%
“…Some of the most abundant fungal genera found in the present study, including Fusarium , Epicoccum , Acremonium , Sarocladium , and Phoma had been reported as endophytes isolated from maize (Pan and May, 2009; Amin, 2013; Xing et al, 2018). In particular, Fusarium , Epicoccum , and Phoma were reported as the most abundant endophytes isolated from maize leaves, using two different lineages (Szilagyi-Zecchin et al, 2016), while Acremonium was detected exclusively in Fusarium wilt suppressive soils, but not in conducive soils (Siegel-Hertz et al, 2018).…”
Section: Discussionsupporting
confidence: 52%
“…A study by Hill and Lacey (1983) demonstrated the prevalence of yeast-like fungi on the surface of ripening barley as well as the leaf pathogen Alternaria alternata . A study by Xing et al (2018) analyzed the mycobiota of maize kernels stored at room temperature between 6 months and 12 years. Fungi were isolated from both the seed surface and within the kernel using similar methodology to our study.…”
Section: Discussionmentioning
confidence: 99%